139k views
2 votes
Write in simplest form using positive exponents in the answer:a^-6/a (a^-3)^2/a^-3

User Lauralea
by
5.9k points

1 Answer

6 votes

a^(-x)=((1)/(a)^{})^x

So:


a^(-6)=((1)/(a))^6

Now:


(a^(-6))/(a)=((1)/(a))^6\cdot(1)/(a)=((1)/(a))^(6+1)=((1)/(a))^7=(1)/(a^7)
(a^(-3))^2=a^(-3\cdot2)=a^(-6)


\frac{\mleft(a^{\mleft\{-3\mright\}}\mright)^2}{a^(-3)}=(a^(-6))/(a^(-3))=(1)/(a^6)\cdot(1)/(a^(-3))=(1)/(a^(6-3))=(1)/(a^3)

When you invert a fraction, you change the sign of the exponent.

User XQbert
by
5.8k points